Tor Aulin och det svenska musiklivet : Några punktbelysningar - Wallner, Bo (Danish Yearbook of Musicology, 1981)
The article describes Tor Aulin’s background and, in the absence of a full-scale study of the composer, contributes material to his biography. At the turn of the century musical life in Scandinavia was dominated by such great names as Sinding, Nielsen and Sibelius - and in Sweden by Peterson-Berger, Stenhammar and Alfven; but a contemporary figure such as Aulin, by virtue of his talent as a composer and his contribution to various aspects of Swedish musicallife both as conductor and performer, is also derserving of attention.